Chromosomal mapping of 170 BAC clones in the ascidian Ciona intestinalis - Shoguchi, Eiichi; Kawashima, Takeshi; Satou, Yutaka; Hamaguchi, Makoto; Sin-I, Tadasu; Kohara, Yuji; Putnam, Nik; Rokhsar, Daniel S.; Satoh, Nori

(untitled) (Genome Research, 2006)
The draft genome (∼160 Mb) of the urochordate ascidian Ciona intestinalis has been sequenced by the whole-genome shotgun method and should provide important insights into the origin and evolution of chordates as well as vertebrates. However, because this genomic data has not yet been mapped onto chromosomes, important biological questions including regulation of gene expression at the genome-wide level cannot yet be addressed. Here, we report the molecular cytogenetic characterization of all 14 pairs of C. intestinalis chromosomes, as well as initial large-scale mapping of genomic sequences onto chromosomes by fluorescent in situ hybridization (FISH). Two-color FISH using 170 bacterial artificial chromosome (BAC) clones and construction of joined scaffolds using paired BAC end sequences allowed for mapping of up to 65% of the deduced 117-Mb nonrepetitive sequence onto chromosomes. This map lays the foundation for future studies of the protochordate C. intestinalis genome at the chromosomal level.